Kontruksi Identitas Virtual Androgini di Media Sosial Instagram - Devi Widiyawati (Peneliti.net, 2021)
Entering the virtual world sometimes also involves openness in one's identity as well as directing how the individual identifies or constructs himself in the virtual world. Virtual identity is seen from activities in building networks, making friends, and ultimately expressing feelings virtually in the communication process. Sandra Bem explains extensively about gender which she describes as a journal that describes an inventory of gender measurements named, The Bem Sex Role Iventory (1974). Where one of these inventories is gender androgynous. This androgynous gender identity looks very attached to someone named Jovi Adhiguna Hunter. Jovi adhiguna Hunter is an influencer from Indonesia who presents his figure as someone who is part of the androgynous gender. The androgynous virtual identity he brought to life through Instagram's social media. This type of research used in this research is descriptive qualitative. This research is used to find out how the construction of identity Androgyny Virtual Identity Construction in Instagram Social Media. Where the data obtained through documentation techniques and online data tracing. Furthermore, the research results explain that Instagram social media can construct androgynous identity through visible visualization by uploading photos and videos. Jovi Adhiguna's androgynous virtual identity is often displayed on Instagram social media, for example through how to dress, make up or make-up, accessories, aya or pose like an androgynous person. Keywords: Virtual Identity Construction, Androgyny, Jovi Adhiguna Hunter, Instagram social media.